(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Tourism has emerged as a thriving global industry. With its tropical allure, the Andaman & Nicobar Islands have become a sought-after destination in India. Despite its appeal, the islands have experienced tourist fatalities, raising concerns for the tourism authorities and the nation. This study aimed to examine the trends associated with tourist fatalities brought for medicolegal autopsy at ANIIMS and GB Pant Hospital, Port Blair, to highlight the causes of death and recommend strategies to prevent such unfortunate incidents. This retrospective study examines medicolegal autopsy records of tourist deaths over eight years (July 2015 to June 2023). Data were collected from police inquest forms and autopsy reports. This study investigates 22 tourist deaths between July age groups of 41-50 and 61-70 years. The highest number of deaths occurred in 2017. Most tourists were Indian (90.9%), with incidents mainly occurring at hotels (68.2%), followed by during travel or sightseeing (18.2%), and lastly activities (13.6%). The majority of incidents occurred during the day (63.3%). Natural deaths were the most common, with cardiovascular pathology being the major cause, followed by accidental and suicidal deaths. Most of the natural deaths had known pre-existing diseases (87.5%). Water safety and scuba-diving activities were highlighted as significant concerns among preventable accidents, while all suicidal deaths occurred in hotel rooms. Collaboration between various agencies can ensure tourist well-being and safety, the authors have provided recommendations in this regard.